The applicability of Sonic hedgehog in mixed type basal cell carcinoma - Sari, Zahra Ayu Lukita; Yahya, Yulia Farida; Toruan, Theresia Lumban (UI Scholars Hub, 2020)
Background: Basal cell carcinoma (BCC) is the most common skin malignancy found in nonmelanoma skin cancer. There are multiple factors contribute to risks for BCC but the underlying mechanism is genetic alteration. The Sonic hedgehog (SHH) pathway is implicated in the etiology of the most common BCC. We reported BCC nodular type in the tip of nasal region with increase SHH. Case Illustration: 50 years old man, presented with hyperpigmented tumor on the nasal tip which easily bleed since 6 months ago. Dermatological examination: the tip of nasal region: a solitaire irregular immobile hyperpigmented tumor, with the size of 2x1x0,3 cm, pearly border with rubbery consistency. Dermoscopy examination found multiple blue-gray globule and telangiectasia feature. Histopathology examination found nodule and micronodule with palisade feature in the periphery and “slit like retraction” in central. Immunohistochemistry examination found more than 50% cell show SHH expression. Wide surgical excision was done with tumor margin 3 mm. Discussion: The hedgehog (Hh) pathway known have important role in embryonic development, that responsible for patterning development organ and tisuue. SHH is one protein ligand that most study and well known in Hh pathways. Conclusion: Activating SHH pathway can resulting in unrestricted SMO activity that causes uncontrollable cell proliferation and eventually carcinogenesis. Increased expression of SHH can be used as a marker in aggresivity of BCC.